Analisis Serapan Hara Nitrogen dan Fosfor Tanaman Kedelai - Asrijal Asrijal; Ambo Upe (Universitas Hasanuddin, 2018)
Experimental research will be executed on farm of rice field sample in BPP Palaguna at Wajo Regency. Obstetrical nutrients Analysis of crop and soil will be done in soil Fertility Laboratory, soil sciences department of Faperta Unhas. This Research aim to analyze the ability of nutrients absorption of soy and maize with the mulch application on rice field rainfed. Research will be done/conducted by using Factorial Device in Group ( RDG). First Factor that is crop type with three treatment level that is L1 = Soy; L2 = Maize; and L3 = Maize + Soy. Second Factor is with mulch (M1) and without mulch (M0). Every treatment unit repeated by 3 times, so there are 18 plot, added a plot which is not cultivated as control for the perception of dynamics of Nitrogen (N) and Phosphorous (P) without palawija cultivation. Reason of the crop election for example because both types of the crop have their own system of root and different morphology characteristic which their possibility will influence the ability of conservation N. Result of analysis indicate that ability of absorption of N and P of maize and soy is better with the mulch application on rice field rainfed